The customer is always dwight how to achieve 100% quality the first time, every time - Sachs, Andrew; LLoyd, John; Garden, Graeme (London : Video Arts, 1988)
Every department or process must be directly responsible for product quality, to achieve one hundred percent quality requires everyone in the process treating the next person in line as customer
Keywords: Customer services; Quality of products